064WS How to Use the GRADE "Evidence-to-Recommendations Framework" to Develop Guideline Recommendations for Therapeutic Interventions. (15th August 2013) - Schunemann, H; Brignardello-Petersen, R; Chan, W; Alonso-Coello, P; Koster, M; Robbins, C
Abstract : Background: Moving from evidence to recommendations in guideline development requires balancing evidence quality with the benefits and harms of therapeutic interventions, patient preferences, and resource and cost considerations. The GRADE Working Group has developed an approach to integrate these factors into development of clinical practice recommendations that is currently further defined in the DECIDE (Developing and Evaluating Communication Strategies to Support Informed Decisions and Practice Based on Evidence) project. Objectives/Goal: To train guideline developers and those working with guideline panels to facilitate the decision-making process for development of recommendations for therapeutic interventions using the GRADE "Evidence-to-Recommendations Framework." Target Audience: Guideline developers, especially those working with guideline panels to develop recommendations for clinical practice. Description of the Workshop and of the Methods used to Facilitate Interactions: An overview of the GRADE "Evidence-to-Recommendations Framework" will be followed by facilitated small group work to develop guideline recommendations. Participants will work together in a simulated guideline panel, and be asked to develop guideline recommendations taking into consideration the quality of evidence from a GRADE evidence summary profile, the balance of benefits vs. harms of an intervention, patient preferences and resource implications. Facilitators will guide the small workgroups through the decision-making process using materials from recent examples of guidelines developed using the "Evidence-to-Recommendations Framework."